An Advanced Transcriptional Response to Corticosterone After Single Prolonged Stress in Male Rats - Ding, Jinlan; Chen, Xinzhao; Han, Fang; Meijer, Onno C. (Frontiers in Behavioral Neuroscience, 2021)
Stress-related neuropsychiatric disorders are often accompanied by dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis. In patients suffering from post-traumatic stress disorder (PTSD), increased sensitivity of glucocorticoid negative feedback has regularly been observed. The single prolonged stress (SPS) paradigm was developed to model increased negative feedback and other aspects of PTSD in rats. In this study, we used a setup that precluded the evaluation of negative feedback but rather served to test the hypothesis of the enhanced glucocorticoid receptor (GR) signaling in higher brain areas. We injected corticosterone or vehicle 7 days after SPS and evaluated plasma corticosterone, as well as gene expression in the dorsal hippocampus and amygdala. We observed a strikingly rapid change in the expression of established GR target genes (t = 30 min) only in the SPS group on exogenous corticosterone injection. Our results extend the notion of increased GR sensitivity in PTSD to include transcriptional responses in the hippocampus.